Fantômes et contrefaçons dans l’oeuvre de Béroalde de Verville : ouvrages virtuels, fictifs et fictionnels - Polizzi, Gilles (Renaissance and Reformation / Renaissance et Réforme, 2011)
This article proposes to take inventory of and examine, in the abundant vervilienne production, the absent works, non-existent or “disguised.” Reflecting upon the relationship between title and identity, as well as our aptitude to deduce from a title the content and character of a work, the author of this article defines the process of “bibliographical illusion,” used frequently by Verville, who, in his bibliography, multiplies these ghosts. Hence, this article sorts the works while considering, in an approximately chronological order, virtual books (announced, but not published and perhaps not written), fictitious books (those whose title suggests camouflage or forgery), and invented disguises; because the science of the book is fueled by invention. This article concludes with the unexpected restoration of a book as real, from the category of fictitious works. Bibliography is then not only the art of listing titles, but also the art and the science of linking titles with works the art of testing the game of bookish inventions and trickery.